Penerapan Taksonomi Bloom sebagai Alat Evaluasi di SDN Kapuk 15 - Magdalena, Ina; Septina, Yulia; Rahmayani, Lusy Nur; Nasrullah, Alim Aqil; Nokhriyana, Aditya Dwi; Pamungkas, Sri Wulandari (Lembaga Yasin AlSys, 2022)
By conducting this research, it is hoped that we can apply Bloom's taxonomy as an evaluation tool and analyze it. Finding out more in-depth information about bloom's taxonomy and learning evaluation. In this research, the type used is a type of qualitative research. in research, for data collection the authors collect through observations to schools, teacher interviews, and documentation. Data analysis techniques were carried out according to the analytical method of Milles and Huberman. In this method there are 3 stages, namely data reduction, data presentation, data verification. in the results of the interviews the teacher actually understood and understood these three domains and the teacher used evaluation very well, but it's just that the teacher was still unfamiliar with